USM, HEC, SOL DISCUSSED LONG-TERM COLLABORATION AND PARTNERSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 29 March 2017 – Universiti Sains Malaysia (USM) has always opened its doors to forge linkages and partnerships with institutions and organisations all over the world, as part of its internationalisation efforts to ensure that the university will always be respected, referred and remain relevant.